AN ANALYSIS OF MULTIMODAL IN BEAUTY PRODUCT ADVERTISEMENTS - Fauziyyah Amatullah; Rusdi Noor Rosa; Fitrawati Fitrawati (Universitas Negeri Padang, 2019)
AbstractMulitimodal is a study that analyzes the meaning of text containing two or more semiotic systems; linguistic, visual, audio, gesture and place. Analyzing multimodal through semiotic approach has been used in the analysis of cover magazine (Gill, 2015), mascara advertisement (Baykal, 2016), cartoon movie (Wulan, 2017), and music video (Brady, 2015). Meanwhile, in this research the writer analyzes multimodal in beauty product advertisement especially lipstick product. This research is intended to, 1) investigate how verbal and visual elements conveyed meanings in both Wardah Lip Cream Matte Lipsticks and Purbasari Hi Matte Lip Cream advertisements. 2) find the comparison between verbal and visual elements used in Wardah Exclusive Matte Lip Cream and Purbasari Hi Matte Lip Cream advertisements. This research used descriptive qualitative method. Based on the data of analysis, it reveals that the visual and verbal processes of these advertisements are in harmony and they complement each other to give a complete message to the audience. The analysis also reveals the similarities of these two advertisements in the three level of metafunctions. In ideational metafunction the most dominant processes used are material and attributive processes, for interpersonal metafunction the most dominant mood used is declarative and for textual metafunction the most dominant theme used is unmarked topical theme.Keywords: Advertisement, beauty product, multimodal analysis, verbal element, visual element.